2009
DOI: 10.1270/jsbbs.59.621
|View full text |Cite
|
Sign up to set email alerts
|

Allelic variation of row type gene Vrs1 in barley and implication of the functional divergence

Abstract: Domesticated barleys produce either two-or six-rowed spikes, whereas their immediate wild ancestor, wild barley, is monomorphic for the two-rowed type. The six-rowed spike is a recessive character, conditioned by a major gene at the vrs1 locus. The wild-type (two-rowed) gene includes a homeodomain-leucine zipper I (HD-Zip I) sequence (HvHox1). The correspondence between peptide sequence and some spike variants was studied by re-sequencing the HvHox1 sequence across a large sample of both wild and domesticated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…To infer the origin of the deficiens allele (Vrs1.t1), we reanalyzed the sequence of the Vrs1 region (2,062 bp length) from 321 domesticated barley and 136 wild barley accessions (Saisho et al, 2009). Haplotype network analysis revealed that the Vrs1.t1 allele (haplotype 10) was derived from the Vrs1.b2 allele (haplotype 6) through a single nucleotide substitution in exon 3, which resulted in the S184G amino acid substitution, implying that Vrs1.b2 was the immediate ancestral allele of Vrs1.t1 (Fig.…”
Section: The Origin Of Deficiens Barleymentioning
confidence: 99%
See 1 more Smart Citation
“…To infer the origin of the deficiens allele (Vrs1.t1), we reanalyzed the sequence of the Vrs1 region (2,062 bp length) from 321 domesticated barley and 136 wild barley accessions (Saisho et al, 2009). Haplotype network analysis revealed that the Vrs1.t1 allele (haplotype 10) was derived from the Vrs1.b2 allele (haplotype 6) through a single nucleotide substitution in exon 3, which resulted in the S184G amino acid substitution, implying that Vrs1.b2 was the immediate ancestral allele of Vrs1.t1 (Fig.…”
Section: The Origin Of Deficiens Barleymentioning
confidence: 99%
“…A haplotype analysis was performed based on resequencing data of the Vrs1 locus (2,062 bp) from 321 domesticated barley accessions and 136 wild barley accessions (Supplemental Table S8; Saisho et al, 2009). Sequence alignments were performed with ClustalW using MEGA7 software (Kumar et al, 2016).…”
Section: Haplotype Analysismentioning
confidence: 99%
“…Previous studies suggested that six-rowed barley evolved from domesticated two-rowed barley through spontaneous mutation (Harlan 1968;Zohary and Hopf 2000;Komatsuda et al 2007). Recently, the function of vrs1 has been further clarified, the wild-type Vrs1 allele (for two-rowed barley) encodes a transcription factor that includes a homeodomain leucine zipper I sequence (HvHox1) (Komatsuda et al 2007;Saisho et al 2009). Expression of Vrs1 was strictly localized in the lateral-spikelet primordia of immature spikes (Komatsuda et al 2007;Saisho et al 2009;Youssef et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the function of vrs1 has been further clarified, the wild-type Vrs1 allele (for two-rowed barley) encodes a transcription factor that includes a homeodomain leucine zipper I sequence (HvHox1) (Komatsuda et al 2007;Saisho et al 2009). Expression of Vrs1 was strictly localized in the lateral-spikelet primordia of immature spikes (Komatsuda et al 2007;Saisho et al 2009;Youssef et al 2012). Loss of function of Vrs1 allele resulted in complete conversion of the rudimentary lateral spikelets in two-rowed barley into fully developed fertile spikelets in the six-rowed phenotype (Komatsuda et al 2007;Saisho et al 2009;Youssef et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…spontaneum accession OUH602 (the OU numbers relate to the Barley and Wild Plant Resource Center collection, http://www.rib.okayama-u.ac.jp/barley/index.html), was obtained from the Institute of Plant Science and Resources, Okayama University, Kurashiki, Japan. The SV numbers represent designators within a core collection designed to capture the global diversity of barley (Saisho et al 2009;Nair et al 2010). Grain of the cultivars "Azumamugi" (AZ), "Kanto Nakate Gold" (KNG), and "Golden Promise" (GP) were supplied by the NIAS Gene Bank, Tsukuba, Japan, that of …”
mentioning
confidence: 99%